The Relationship between Work-Family Conflict, Job Demands, and Resilience towards Job Burnout among Nurses in Selangor - Kwong, Bi Ying; Nasuredin, Juzaimi (Research in Management of Technology and Business, 2023)
The growing rate of occupational stress was rising, and burnout in healthcare has become a global concern. Burnout among healthcare professionals was now recognized as a significant public health issue. Most people who work in health care, especially nurses, had vital in preventing and controlling infections, isolating patients, and purposes outbreaks. The study identified the relationship between work-family conflict, job demands, and resilience toward job burnout among Selangor nurses. The quantitative method was used in the research. The survey has been conducted in Selangor, and the response rate was 210 respondents. Both primary and secondary data were used in this research. The information gathered from the online surveys was analyzed using Microsoft Excel and the Statistical Package for Social Science (SPSS) to obtain reliable findings for the data analysis process. The findings show that there was a relationship between work-family conflict, job demand, resilience, and job burnout. According to the data analysis, the result showed a positive correlation which was a positive relationship between work-family conflict, job demand, resilience, and job burnout. Most medical healthcare workers were burnt out, and their "voices of fatigue" had been louder on social media. However, this study had to be conducted in a big area and in more hospitals. The Malaysian Ministry of Health used this research’s results to comprehend better the existing situation and craft initiatives to lessen healthcare professionals’ feelings of burnout. This created awareness for the public about the problems or challenges in the healthcare sector.